Treatment of ingrown nail using CO2 laser – four-year own experience - Kozłowska-Geller, Monika A. (Medical Studies/Studia Medyczne, 2016)
Introduction : Ingrown toenails are one of the most common nail disorders, with complex and multifactorial causes, for all age groups, mostly young adults. The essence of disease is congenital or acquired distortion of the proportions between the size of the nail bed and the nail folds. Laser treatment consists of the vaporisation of the matrix and bed, i.e. the reproductive sphere of the nail, using a CO 2 laser. Aim of the research : Evaluation of the effectiveness of laser dissection using a CO 2 laser. Material and methods: The methodology was divided into two stages. The first stage consisted of a retrospective analysis of the medical documentation of 165 patients who had undergone laser CO 2 dissection, during the period from February 2011 to May 2015 in the Laser CO 2 Surgery Room, according to the developed scheme. The second stage was follow-up control of patients participating in the study, a week and then a month after surgery. In addition, in May 2015 90 patients were audited in terms of effectiveness and satisfaction of the treatment and recurrence of symptoms. The remaining 70 patients answered these questions by telephone. Results and conclusions: Laser dissection of the ingrown nail with matrixectomy is a very effective method, only in 4 (2%) patients was there a recurrence. Nearly 90% of patients expressed satisfaction with the outcome of the surgery. The cause of dissatisfaction was sometimes an anaesthetic appearance of the nail apparatus. Nearly 70% of patients were children and young adults aged up to 23 years. The most frequent cause of ingrown toenail was wearing inappropriate shoes and incorrect cutting of toenails.